Is it possible to decolonize the concept of cultural anthropophagy?” - Clavo, María Iñigo (DAT Journal, 2020)
The article analyzes the origins of the Anthropophagy category that arises at the beginning of the 20th century based on Oswald de Andrade’s elaboration and asks about the possibility or impossibility of its re-elaboration in the contemporary curatorial context in connection with the category of decolonization. August 12, 2016.